2005
DOI: 10.1111/j.1365-2036.2005.02520.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: practical management of inflammatory bowel disease patients taking immunomodulators

Abstract: SUMMARYAzathioprine, mercaptopurine, methotrexate, ciclosporin and tacrolimus all have their respective niches in the treatment of inflammatory bowel disease. These immunomodulators are potent and effective medications; however, they potentially have serious toxicity. To maximize benefit and minimize risk, clinicians must understand the mechanism of action, appropriate indications, range of toxicity and proper dosing of these medications. Furthermore, once initiating therapy, patients need to be monitored appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 130 publications
0
60
0
1
Order By: Relevance
“…CsA is a cyclic peptide which is produced as a metabolite by the fungus Tolypocladium inflatum and can be used as an immunosuppressive agent to prevent rejection after organ transplantation as well as for the treatment of chronic inflammatory diseases (Kountouras et al 2004;Meijssen 1998). It also inhibits the production of IL-2 by activated T lymphocytes through a calcineurin-dependent pathway (Pino-Lagos et al 2010;Siegel and Sands 2005). UC patients with severe steroid-refractory disease are often treated with CsA as a rescue medication to avoid an otherwise necessary colectomy.…”
Section: Introductionmentioning
confidence: 99%
“…CsA is a cyclic peptide which is produced as a metabolite by the fungus Tolypocladium inflatum and can be used as an immunosuppressive agent to prevent rejection after organ transplantation as well as for the treatment of chronic inflammatory diseases (Kountouras et al 2004;Meijssen 1998). It also inhibits the production of IL-2 by activated T lymphocytes through a calcineurin-dependent pathway (Pino-Lagos et al 2010;Siegel and Sands 2005). UC patients with severe steroid-refractory disease are often treated with CsA as a rescue medication to avoid an otherwise necessary colectomy.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that 6-MMP concentrations Ͻ5700 pmol/8 ϫ 10 8 Ery were less often associated with increased transaminase activities (10 ). However, these results from pediatric studies have not been confirmed in adults (19 ), and caution is warranted regarding premature dose adjustments (21 ).…”
mentioning
confidence: 99%
“…The role of 6-TGN for assessing compliance, and in combination with 6-MMP to assess drug-failure attributable to high methylator status, seems well accepted (21,22 ) but not yet substantiated by rigorous study data.…”
mentioning
confidence: 99%
“…Individuals with low or undetectable TPMT activity are at high risk for developing life-threatening myelosuppression at standard doses of thiopurine drugs (7,8 ). Patients with high TPMT activity may experience treatment failure (9,10 ) or hepatotoxicity (11 ), but the situation is much less clear than for the TPMT deficiencies (12)(13)(14). In addition, an estimated 10% to 30% of patients cannot tolerate AZA therapy because of nonmyelosuppression adverse reactions, such as influenzalike symptoms, nausea, vomiting, hepatotoxicity, pancreatitis, fever, or rash (1,12,15,16 ).…”
mentioning
confidence: 99%